Factors influencing adherence to the new intermittent preventive treatment of malaria in pregnancy policy in Keta District of the Volta region, Ghana - Alren O. Vandy; Nana Yaw Peprah; Joseph Yaw Jerela; Perfect Titiati; Abubakar Manu; Joseph Akamah; Ernest T. Maya; Kwasi Torpey (BMC, 2019)
Abstract Background About 25% of pregnant women in malaria-endemic areas are infected with malaria and this accounts for about 15% of maternal deaths globally. Intermittent preventive treatment in pregnancy with sulfadoxine-pyrimethamine (IPTp-SP) is one of the main strategies for prevention of malaria in pregnancy. A new recommendation was made by the World Health Organization (WHO) that at least three doses of IPTp-SP should be administered before delivery. This study sought to determine the factors influencing adherence to the new IPTp-SP policy in Keta District, Volta region, Ghana. Methods A cross-sectional quantitative study among 375 nursing mothers at four selected health facilities in Keta district, Ghana was conducted using a structured questionnaire to interview participants. Sampling proportionate to the size of facility was used to determine the number of nursing mothers from each facility based on the caseload. For each facility systematic random sampling was used to select eligible nursing mothers. Data was analyzed using STATA 15. Chi-square was used to test bivariate association between categorical variables and adherence. Logistic regression analysis was used to examine sociodemographic, individual and institutional factors influencing adherence to IPTp-SP. Result About 82.1% of participants adhered to the WHO policy recommendations of at least three doses of IPTp-SP. However, only 17.1% received Ghana's five dose coverage recommendation. The proportion of IPTp-SP coverage for IPTp1 was 98.9%; IPTp2 95.5%; IPTp3 80.8%; IPTp4 39.5%; IPTp5 17.1%. Conclusion Adherence to IPTp-SP was satisfactory according to WHO's policy recommendation, however, majority of the participants had less than the five doses recommended in Ghana. Number of Antenatal Care (ANC) visits and knowledge of malaria were the main determinants of adherence to IPTp-SP.